2013
DOI: 10.3892/ijo.2013.2034
|View full text |Cite
|
Sign up to set email alerts
|

MiR-15a is underexpressed and inhibits the cell cycle by targeting CCNE1 in breast cancer

Abstract: MicroRNAs (miRNAs) are a small class of non-coding RNAs that are widely dysregulated in various cancers. They act as either oncogenes or tumor suppressor genes in human cancer. The purpose of this study was to examine the expression levels of miR-15a in human breast cancer and its potential role in disease pathogenesis. The expression levels of miR-15a were measured by quantitative polymerase chain reaction (qPCR) in 40 breast cancer specimens and adjacent normal breast tissues. MTT assays, colony formation as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
56
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 24 publications
1
56
0
2
Order By: Relevance
“…Previous reports have also demonstrated that the miR-15a/16-1 miRNA cluster functions as a tumor suppressor, targeting Bcl-2 protein in prostate tumor cells (21)(22)(23)32,33). Inhibition of cell proliferation by miR-15a/16-1 has been reported to occur in both lymphoid and nonlymphoid tissue (21-23,32,33,37,38), Wang et al (40) further demonstrated the miR15a level is increased and it induces cell death in an ischemia reperfusion model (39,41). Our current studies revealed a differential effect of miR-15a/16 on apoptosis in nontumor lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have also demonstrated that the miR-15a/16-1 miRNA cluster functions as a tumor suppressor, targeting Bcl-2 protein in prostate tumor cells (21)(22)(23)32,33). Inhibition of cell proliferation by miR-15a/16-1 has been reported to occur in both lymphoid and nonlymphoid tissue (21-23,32,33,37,38), Wang et al (40) further demonstrated the miR15a level is increased and it induces cell death in an ischemia reperfusion model (39,41). Our current studies revealed a differential effect of miR-15a/16 on apoptosis in nontumor lung epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-15a/16 also targets cell cycle regulators. Inhibition of miR-15 expression enhances cyclin E1 mRNA and protein levels (41). Inhibition of both miR-15 and 16 expression augments G 1 /S transition, while overexpression of miR-15 reduces cyclin E protein levels and inhibits the G 1 /S transition (42).…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al revealed that overexpression of miR-15a inhibited cellular growth, suppressed migration and arrested cells at the G1 phase, but did not promote cellular apoptosis (Luo et al, 2013). Cai et al found that miR-15a downregulate CCND1 and induce apoptosis and cell cycle arrest in osteosarcoma (Cai et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been shown that HER2Δ16 (a clinically important oncogenic isoform of HER2) can suppresses miR-15a (Cittelly et al, 2010). In addition, miR-15a was shown to mediate cell cycle arrest and promoting cell apoptosis of breast cancer by directly targeting Cyclin E1 suggesting the tumor suppressive activity of miR-15a in a breast cancer cell line (Luo et al, 2013;Shinden et al, 2015). Moreover, the identification of HER2/neu-induced miR-15a repression provides a greater understanding into how HER2/neu overexpression promotes invasion and significantly differentially expressed miR-335 and miR-24 upon non-IBC groups based on menopausal status and miR-342-5p based on parity profile; B) the fold change of the significantly differentially expressed miR-15a and miR-24 upon IBC groups according to HER-2 and menopausal status respectively.…”
Section: Discussionmentioning
confidence: 99%